A FRAMEWORK TO DESIGN MASCOT CHARACTER AS SUPPORTING TOOL FOR CITY BRANDING BASED ON YURU-CHARA CONCEPT - Wiratmo, Triyadi Guntur; Grahita, Banung; Maslan, Riama; Fadillah, Fadillah; Ratri, Dianing (Dian Nuswantoro University, 2021)
AbstrakPemanfaatan maskot, yang juga disebut